Multicasting gathers steam. (support for Internet Protocol multicasting; Tibco ships TibNet) (Company Business and Marketing) - Janah, Monua (InformationWeek (Manhasset, N.Y.), 1996)
Tibco, a subsidiary of Reuters, is developing a line of Tibnet products that employ 'publish and subscribe' technology to enable IP multicasting. Several companies are supporting Tibnet protocols in their own products. These companies include Sun Microsystems, Informix, Netcom and JavaSoft. Cisco Systems will include the protocols in the next version of its Internetwork Operating System. Multicasting simultaneously sends packets to several IP address in order to conserve bandwidth. The publish and subscribe technology facilitates the sharing of data between applications. Tibco plans to submit the technology to the Internet Engineering Task Force in early 1997 for consideration as an Internet standard.